Biomonitoring of human exposures to chlorinated derivatives and structural analogs of bisphenol A - Andra, Syam S.; Charisiadis, Pantelis; Arora, Manish; Van Vliet-Ostaptchouk, Jana V.; Makris, Konstantinos C. (My University, 2015)
The high reactivity of bisphenol A (BPA) with disinfectant chlorine is evident in the instantaneous formation of chlorinated BPA derivatives (ClxBPA) in various environmental media that show increased estrogen-activity when compared with that of BPA. The documented health risks associated with BPA exposures have led to the gradual market entry of BPA structural analogs, such as bisphenol S (BPS), bisphenol F (BPF), bisphenol B (BPB), etc. A suite of exposure sources to ClxBPA and BPA analogs in the domestic environment is anticipated to drive the nature and range of halogenated BPA derivatives that can form when residual BPA comes in contact with disinfectant in tap water and/or consumer products. The primary objective of this review was to survey all available studies reporting biomonitoring protocols of ClxBPA and structural BPA analogs (BPS, BPF, BPB, etc.) in human matrices. Focus was paid on describing the analytical methodologies practiced for the analysis of ClxBPA and BPA analogs using hyphenated chromatography and mass spectrometry techniques, because current methodologies for human matrices are complex. During the last decade, an increasing number of ecotoxicological, cell-culture and animal-based and human studies dealing with ClxBPA exposure sources and routes of exposure, metabolism and toxicity have been published. Up to date findings indicated the association of ClxBPA with metabolic conditions, such as obesity, lipid accumulation, and type 2 diabetes mellitus, particularly in in-vitro and in-vivo studies. We critically discuss the limitations, research needs and future opportunities linked with the inclusion of ClxBPA and BPA analogs into exposure assessment protocols of relevant epidemiological studies.
Keywords: Analogs; Bisphenol A; Biomonitoring; BPA analogs; Chlorinated derivatives; BPA free; Emerging contaminants; Disinfection; Mass spectrometry; Human exposure; Metabolites